132 Clinical characteristics and outcomes of a contemporary, real-world, single-centre cohort of patients with advanced heart failure. (8th December 2021) - Pagnesi, Matteo; Lombardi, Carlo M.; Tomasoni, Daniela; Tedino, Chiara; Maggi, Giuseppe; Donina, Francesco; Giozani, Federico; Galperti, Maria Teresa; Calì, Filippo; Bognoni, Ludovica; Colombo, Giada; Cani, Dario; et al.
Abstract: Aims: An increasing number of patients with heart failure (HF) progresses to an advanced stage, characterized by persistent and sever symptoms and worse prognosis. A detailed characterization of patients with advanced HF is needed to optimize clinical management and timely refer for heart transplant or left ventricular assist device implantation. Methods and results: A retrospective analysis was performed on patients with HF who were admitted to hospital or performed an outpatient visit at our centre (Spedali Civili di Brescia, Brescia, Italy) from 1 January 2020 to 31 December 2020, and who had at least one of the following high-risk characteristics: (1) previous or ongoing requirement for inotropes; (2) persisting New York Heart Association (NYHA) class III or IV and/or persistently high natriuretic peptides (BNP or NT-proBNP); (3) end-organ dysfunction, defined as worsening renal or liver dysfunction in the setting of HF; (4) ejection fraction (EF) <20%; (5) recurrent appropriate defibrillator shocks; (6) more than 1 hospitalization for HF in the last year; (7) persisting fluid overload and/or increasing diuretic requirement; (8) consistently low blood pressure (systolic blood pressure <90–100 mmHg); and (9) inability to up-titrate or need to decrease/cease HF therapies, such as beta-blockers, angiotensin-converting enzyme inhibitors, angiotensin receptor-neprilysin inhibitors, or mineralocorticoid receptor antagonists. The updated 2018 Heart Failure Association (HFA)—European Society of Cardiology (ESC) criteria for defining advanced HF were evaluated. The primary endpoint was all-cause mortality; secondary endpoints were a composite of all-cause mortality or hospitalization for HF and a composite of all-cause mortality or hospitalization for any reason. Among 493 patients with HF who were hospitalized or performed an outpatient visit in 2020, 230 (46.7%) had at least one high risk criterion and were included in the study. Mean age was 75.5 ± 11.9 years, 156 patients (67.8%) were men, and 160 patients (69.6%) were hospitalized and included as inpatients. Median EF was 38% [interquartile range (IQR): 25–50%] and 117 patients (50.9%) had HF with reduced EF (<40%); median NT-proBNP was 4044 (IQR: 2262–7664) pg/mL. Among the included 230 patients, 38 (16.5%) had all four updated HFA-ESC criteria defining advanced HF, 53 (23.0%) had American College of Cardiology (ACC)/American Heart Association (AHA) stage D, 21 (9.1%) had INTERMACS profile 1–3. In-hospital mortality was 10.6% (among inpatients). After a median follow-up of 301 (214–442) days, a total of 62 patients died (27.0%), and the secondary endpoints of all-cause death or HF hospitalization and all-cause death or any hospitalization were observed in 107 (46.5%) and 139 (60.4%) patients, respectively. Patients fulfilling all four updated HFA-ESC criteria for advanced HF had a higher risk of all-cause mortality (unadjusted HR: 2.06; 95% CI: 1.18–3.60; P = 0.011), also after adjustment for covariates of interest (adjusted HR: 2.20; 95% CI: 1.03, 4.70; P = 0.041). Conclusions: In our contemporary, real-world cohort of HF patients with high-risk characteristics, mid-term prognosis was poor, and the use of updated HFA-ESC criteria defining advanced HF identified a subset at increased risk of mortality.